Electrocardiographic patterns and systolic and diastolic functions of the heart in the highly trained football players with increased left ventricular mass - Maskhulia, L.; Chabashvili, N.; Akhalkatsi, V.; Chutkerashvili, T. (Georgian Medical News, 2006)
Over the past several years interest regarding the causes of sudden deaths in young trained athletes has heightened in the medical community. 36% of sudden cardiac death (SCD) in young competitive athletes is due to hypertrophic cadiomyopathy (HCM), while 10% of SCD cases in sports are due to increased cardiac mass without signs of HCM. The goal of this study was to evaluate systolic and diastolic functions, and to determine the clinical significance of electrocardiographic patterns in highly trained football players with increased left ventricular mass index (LVMI) > 125g/m(2). 221 highly trained male football players were studied, among them 46 with increased LVMI. M, 2D, Doppler echocardiography and resting and exercise electrocardiography were performed. Various cardiovascular abnormalities were found by echocardiography in 12 athletes (5,4%). Systolic and diastolic functions of the heart were within normal limits. Increased left ventricular mass in the football players was often associated with abnormal ECG patterns (47,8%). Abnormal ECGs were found in 85,7% of football players with concentric hypertrophy. The group of athletes with both increased LVMI and abnormal ECG patterns need further evaluation and observation. ECG and echocardiography should be included in the PPS protocol of the highly trained football players to prevent SCD in young athletes.